SDN TCP-SYN Dataset: A dataset for TCP-SYN flood DDoS attack detection in software-defined networksMendeley Data - Sudesh Kumar; Sunanda Gupta (Data in Brief)
The TCP-SYNC SDN dataset, a collection of labelled network traffic data for investigating DDoS attack detection in Software-Defined Networking (SDN) environments. The dataset includes flow-level metrics from both normal and malicious traffic, particularly TCP-SYN flood attacks. Generated in a controlled testbed using advanced simulation tools Mininet(v2.3.0) and real internet traffic captured from real-world internet browsing sessions via Google Chrome and recorded using Wireshark(v3.0.2), this dataset is essential for researchers and practitioners working on TCP-SYN flood DDoS attack detection and machine learning-based traffic classification. The dataset is publicly available at Mendeley Data.